Protective role of IGF-1 and GLP-1 signaling activation in neurological dysfunctions. (November 2022) - Bhalla, Sonalika; Mehan, Sidharth; Khan, Andleeb; Rehman, Muneeb U.
Abstract: Insulin-like growth factor-1 (IGF-1), a pleiotropic polypeptide, plays an essential role in CNS development and maturation. Glucagon-like peptide-1 (GLP-1) is an endogenous incretin hormone that regulates blood glucose levels and fatty acid oxidation in the brain. GLP-1 also exhibits similar functions and growth factor-like properties to IGF-1, which is likely how it exerts its neuroprotective effects. Recent preclinical and clinical evidence indicate that IGF-1 and GLP-1, apart from regulating growth and development, prevent neuronal death mediated by amyloidogenesis, cerebral glucose deprivation, neuroinflammation and apoptosis through modulation of PI3/Akt kinase, mammalian target of rapamycin (mTOR) and mitogen-activated protein kinase (MAPK/ERK). IGF-1 resistance and GLP-1 deficiency impair protective cellular signaling mechanisms, contributing to the progression of neurodegenerative diseases. Over the past decades, IGF-1 and GLP-1 have emerged as an essential component of the neuronal system and as potential therapeutic targets for several neurodegenerative and neuropsychiatric dysfunctions. There is substantial evidence that IGF-1 and GLP-1 analogues penetrate the blood-brain barrier (BBB) and exhibit neuroprotective functions, including synaptic formation, neuronal plasticity, protein synthesis, and autophagy. Conclusively, this review represents the therapeutic potential of IGF-1 and GLP-1 signaling target activators in ameliorating neurological disorders. Graphical Abstract: ga1 Highlights: IGF-1 and GLP-1 signaling promotes neuronal cell proliferation, growth and CNS development. Dysregulation of IGF-1 and GLP-1 involves in the progression of neurodegenerative and neuropsychiatric disorders. IGF-1 and GLP-1 downregulation is associated with amyloidogenesis, cerebral glucose deprivation, neuroinflammation and apoptosis. Potential IGF-1 and GLP-1 activators exhibit neuroprotective effects in various neurological dysfunctions.